Social Media Analysis for Investigating Consumer Sentiment on Mobile Banking - Alessandra Giovanna Asali (Journal of International Conference Proceedings (JICP), 2021)
This paper is aimed to give more insight for Indonesian banks to understand consumers’ sentiment in social media towards their mobile banking service, determining area(s) that requires improvement, and giving recommendation where refinement is due. Nine highly mentioned mobile banking features in Indonesian language are determined through manual observation on Twitter, translated as: payment, block, open new bank account, login, transaction report, bank balance, top-up, transaction, and transfer. Twitter entries from January 1st, 2019 to December 31st, 2020 which include the words ‘mobile banking’, ‘m-banking’, or ‘mbanking’ plus one of the nine features are collected and classified according to their sentiment. In total, 5014 tweet data are collected. Negative tweets have the biggest proportion at 49.8%, followed by neutral tweets with 44.5% and positive tweets with 5.7% only. Proportion of negative tweets are way higher than the positive tweets for all nine features. From highly mentioned words and representative example tweets, some preferred features can be derived, including no extra fee to access any mobile banking feature, providing record that can be recalled after important transactions, keeping mobile banking app updated to customer needs while also maintaining steadiness, speed, and ease-of-use, along with better synchronization with third party entities.